Metode Shamitah (The Silent Way Method) dalam Pembelajaran Bahasa Arab - Aathifah Al Farros; Masrun (INTIFA: Journal of Education and Language, 2024)
The shamitah method (The Silent Way Method) or better known as the silent teacher method was coined in 1972 by Caleb Gategno, a linguist who applied the principles of cognitivism and philosophy in his teaching. He introduced this method through his book "Teaching Foreign Languages ​​in School: A Silent Way". It is called the silent teacher method because the teacher is more silent than talking during the learning process. This method asks the teacher not to say anything for about 90% of the time allocated for teaching. This method has been widely used in learning foreign languages ​​in the world, including Arabic. The relationship of this method to learning Arabic will initially feel like the process is complex, especially for 'mubtadi' or basic students. This method cannot stand alone without the support of other methods to support the learning process so that it can cover the shortcomings of this shamitah method. This method has its own characteristics, in this method students are expected to be able to discover for themselves what they have captured and repeat it independently during the learning process. Maharah qiroah and maharah Istima' in this case are really needed to support the ongoing implementation of this shamitah method. ABSTRAK Metode shamitah (The Silent Way Method) atau yang lebih dikenal dengan nama metode guru diam ini dicetuskan pada tahun 1972 oleh Caleb Gategno yakni seorang ahli bahasa yang menerapkan prinsip kognitivisme dan ilmu filsafat dalam pengajarannya. Ia memperkenalkan metode ini melalui bukunya “Teaching Foreign Languages in School: A Silent Way”. Dinamakan metode guru diam karena guru lebih banyak diamnya daripada berbicara saat proses belajar berlangsung. Metode ini meminta guru untuk tidak mengatakan apapun sekitar 90% dari alokasi waktu yang dipakainya untuk mengajar. Metode ini telah banyak dipakai dalam pembelajaran bahasa Asing di dunia, termasuk bahasa Arab. Kaitan metode ini pada pembelajaran bahasa Arab awalnya akan merasa prosesnya seakan kompleks, terutama bagi pelajar mubtadi’ atau dasar. Metode ini tidak bisa berdiri sendiri tanpa dukungan metode lain sebagai pendukung proses pembelajaran sehingga dapat menutupi kekurangan yang ada pada metode shamitah ini. Metode ini memiliki ciri khasnya tersendiri, pada metode ini pelajar diharapkan mampu menemukan sendiri apa yang telah tangkap dan dia ulangi secara mandiri selama pembelajaran berlangsung. Maharah qiroah dan maharah Istima’ dalam hal ini sangat dibutuhkan untuk mendukung berlangsungnya penerapan metode shamitah ini.